A cytosolic disulfide bridge‐supported dimerization is crucial for stability and cellular distribution of Coxsackievirus B3 protein 3A. (11th February 2022) - Voss, Martin; Kleinau, Gunnar; Gimber, Niclas; Janek, Katharina; Bredow, Clara; Thery, Fabien; Impens, Francis; Schmoranzer, Jan; Scheerer, Patrick; Kloetzel, Peter‐Michael; Beling, Antje
Abstract : RNA viruses in the Picornaviridae family express a large 250 kDa viral polyprotein that is processed by virus‐encoded proteinases into mature functional proteins with specific functions for virus replication. One of these proteins is the highly conserved enteroviral transmembrane protein 3A that assists in reorganizing cellular membranes associated with the Golgi apparatus. Here, we studied the molecular properties of the Coxsackievirus B3 (CVB3) protein 3A with regard to its dimerization and its functional stability. By applying mutational analysis and biochemical characterization, we demonstrate that protein 3A forms DTT‐sensitive disulfide‐linked dimers via a conserved cytosolic cysteine residue at position 38 (Cys38). Homodimerization of CVB3 protein 3A via Cys38 leads to profound stabilization of the protein, whereas a C38A mutation promotes a rapid proteasome‐dependent elimination of its monomeric form. The lysosomotropic agent chloroquine (CQ) exerted only minor stabilizing effects on the 3A monomer but resulted in enrichment of the homodimer. Our experimental data demonstrate that disulfide linkages via a highly conserved Cys‐residue in enteroviral protein 3A have an important role in the dimerization of this viral protein, thereby preserving its stability and functional integrity. Abstract : Enterovirus, such as Coxsackievirus B3 (CVB3), express the highly conserved transmembrane protein 3A that assists in reorganizing cellular membranes to support viral replication. By applying mutational analysis and biochemical characterization, we demonstrate that protein 3A forms disulfide‐linked dimers via a conserved cytosolic cysteine residue at position 38 (C38). Homodimerization of CVB3 protein 3A via C38 reduces its degradation by the proteasome, thereby preserving the stability of protein 3A.